1997
DOI: 10.1017/s0043174500093097
|View full text |Cite
|
Sign up to set email alerts
|

Germination, emergence, and growth of giant foxtail (Setaria faberi) and fall panicum (Panicum dichotomiflorum)

Abstract: Controlled environment experiments were completed to determine the effect of temperature on giant foxtail and fall panicum germination, emergence, and growth. Giant foxtail seed germination decreased when exposed to a constant 30 C compared to 20 C. Germination also decreased in the alternating 20/30 C temperature regime when the hours of exposure to 30 C as compared to 20 C increased. Fall panicum required alternating temperatures of 14 C (9 h)/28 C (15 h) to germinate. Giant foxtail seed germination exceeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Giant foxtail and redroot pigweed emergence was similar when seeds were sown on the surface or at a 0.5-cm depth (data not shown). Wiese and Davis (1987) and Siriwardana and Zimdahl (1983) concluded that 1 cm was optimal for redroot pigweed emergence, whereas in previous research, emergence of giant foxtail was greatest at a 1 cm depth (Fausey and Renner 1997).…”
Section: -----------------------------------------------------------Nmentioning
confidence: 82%
“…Giant foxtail and redroot pigweed emergence was similar when seeds were sown on the surface or at a 0.5-cm depth (data not shown). Wiese and Davis (1987) and Siriwardana and Zimdahl (1983) concluded that 1 cm was optimal for redroot pigweed emergence, whereas in previous research, emergence of giant foxtail was greatest at a 1 cm depth (Fausey and Renner 1997).…”
Section: -----------------------------------------------------------Nmentioning
confidence: 82%
“…Allelopathic chemicals rarely kill seeds before germination but can act as one of the several factors preventing successful emergence. Many factors associated with tillage promote germination, including exposure to light (Sauer and Struik 1964), increased diurnal temperature fluctuations (Fausey and Renner 1997; Henson 1970), and the venting of volatile germination inhibitors (Holm 1972), and these processes can deplete seedbanks. However, these processes will act about equally whether residues are incorporated during tillage or not.…”
Section: Introductionmentioning
confidence: 99%
“…Fall panicum, a member of the Poaceae family, native to eastern United States and West Indies (Bryson and DeFelice 2009), is the most prevalent and difficult to control annual grass weed in Florida sugarcane (Odero et al 2014). It is a prolific seed producer, and a single plant can produce 10,000 to more than 100,000 seeds depending on plant size (Fausey and Renner 1997; Govinthasamy and Cavers 1995). The variation in fall panicum seed quantity is attributed to seed shattering soon after ripening, which makes estimation of seed number difficult (Govinthasamy and Cavers 1995).…”
Section: Introductionmentioning
confidence: 99%